Public Health, Community Resilience, and Psychosocial Recovery after the 2025 Sumatra Floods and Landslides - Marthoenis, Marthoenis (Asian Journal of Public Health and Nursing, 2025)
Background:The floods and landslides that struck several provinces in Sumatra toward the end of 2025 resulted in substantial loss of life, large-scale displacement, and damage to public infrastructure. As of 29 December 2025, national disaster reports recorded around 1,140 deaths, 163 people missing, and nearly 400,000 displaced residents, with reconstruction needs estimated at approximately 51.82 trillion rupiah. These events underscore the intersection between disaster exposure, public-health system resilience, and psychosocial wellbeing. Objectives:This editorial reflects on the public-health and mental-health implications of the 2025 Sumatra disaster, draws on recent empirical and review evidence, and highlights priorities for strengthening community-based preparedness and recovery. Key Issues:Post-disaster settings are commonly characterized by increased risks of infectious disease, disruption of routine care for chronic and psychiatric conditions, and pressure on primary health-care services. Evidence from flood- and landslide-affected contexts in South and Southeast Asia indicates elevated symptoms of anxiety, depression, sleep disturbance, and post-traumatic stress among survivors, particularly among socio-economically vulnerable households, older adults, women, and adolescents. These psychosocial outcomes are shaped by prolonged displacement, livelihood loss, housing insecurity, and erosion of social support networks. Recommendations and Conclusion:The editorial emphasizes the importance of framing disaster risk reduction as a sustained public-health responsibility grounded in primary care and continuity of essential services, integrating psychosocial and mental-health care across preparedness, response, and recovery, and advancing inclusive, community-driven resilience strategies that prioritize vulnerable populations to protect dignity and wellbeing in future events.